MANGROVE VEGETATION COMMUNITY STRUCTURE IN PONGKAR VILLAGE, TEBING DISTRICT, KARIMUN REGENCY, KEPULAUAN RIAU PROVINCE - Hadiyatma, Patwa; Efriyeldi, Efriyeldi; Thamrin, Thamrin (Asian Journal of Aquatic Sciences, 2023)
Mangrove is a type of vegetation that grows on muddy soil in tidal areas, around the river estuary, and in tropical coastal areas. To support the success of mangrove forest management, it is important to pay attention to the factors that affect the growth of mangroves. This research was conducted in October – December 2021. The purpose of the study was to determine the type, density value, frequency, and cover of mangrove vegetation and its importance value index in Pongkar Village, Karimun Regency, Kepulauan Riau Province, using survey methods and sampling and measuring environmental quality parameters waters in the field. Based on the result of the research, the types of mangrove vegetation found consisted of 6 species, namely Avicennia alba, Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, and Lumnitzera littorea. The highest density of mangrove vegetation in the Pongkar Village area is near the Military District Command (Station II) housing with a total density of 1822.22 ind/ha. The highest relative frequency value of mangroves is found in the Pelambung area of ​​A.alba species with a value of 40%. The highest relative dominance value of mangroves was found at station II of S.alba species with a value of 63.12%. Meanwhile, the highest important value index was found at station II for S.alba species with a value of 152.01% and the lowest important value index was L.littorea which was found at station I with a value of 12.69%.